L‐DOPA functions as a plant pheromone for belowground anti‐herbivory communication. (27th January 2023) - Cascone, Pasquale; Vuts, Jozsef; Birkett, Michael A.; Dewhirst, Sarah; Rasmann, Sergio; Pickett, John A.; Guerrieri, Emilio
Abstract: While mechanisms of plant–plant communication for alerting neighbouring plants of an imminent insect herbivore attack have been described aboveground via the production of volatile organic compounds (VOCs), we are yet to decipher the specific components of plant–plant signalling belowground. Using bioassay‐guided fractionation, we isolated and identified the non‐protein amino acid l ‐DOPA, released from roots of Acyrtosiphon pisum aphid‐infested Vicia faba plants, as an active compound in triggering the production of VOCs released aboveground in uninfested plants. In behavioural assays, we show that after contact with l ‐DOPA, healthy plants become highly attractive to the aphid parasitoid (Aphidius ervi), as if they were infested by aphids. We conclude that l ‐DOPA, originally described as a brain neurotransmitter precursor, can also enhance immunity in plants. Abstract : Using bioassay‐guided fractionation, we isolated and identified the non‐protein amino acid L‐DOPA, released from roots of Acyrtosiphon pisum aphid‐infested Vicia faba plants, as the most active compound in triggering the production of VOCs released aboveground in uninfested plants. Healthy plants after contact with L‐DOPA, by producing specific VOCs, became highly attractive to the aphid parasitoid (Aphidius ervi), as if they were infested by aphids.